Study on the Effectiveness of Integrating Religious Approaches in Health Interventions for Transgender Individuals in Malaysia - Rafidah Hanim Mokhtar; Maliya Suofeiya; Samsul Draman; Irwan Mohd Subri; Fathima Begum Syed Mohideen (International Islamic University Malaysia, 2025)
Index by Scopus (Tier 2)